Female donor to male recipient gender discordance results in inferior graft survival: a prospective study of 1, 042 liver transplants. Issue 4 (30th September 2013) - Croome, Kristopher P.; Segal, Dan; Hernandez‐Alejandro, Roberto; Adams, Paul C.; Thomson, Alan; Chandok, Natasha
Abstract Background The influence of donor‐recipient gender mismatch on outcomes after liver transplantation (LT) is controversial. The aim of this study was to evaluate the effect of donor and recipient gender discordance on graft survival. Methods All patients who underwent primary LT from 1994–2012 at a single‐center were identified prospectively. Clinico‐demographic data were collected at the time of LT and last follow‐up. Gender match included both male donor to male recipient (MM) and female donor to female recipient (FF), while gender mismatch included female donor to male recipient (FM) and male donor to female recipient (MF). Survival curves for graft survival were generated using Kaplan–Meier method and compared by log‐rank test. Unadjusted and multivariate adjusted COX regression analyzing graft survival at up to 10 years post‐transplant was performed. Results A total of 1, 042 subjects fulfilled the criteria. Graft survival in patients receiving a donor‐recipient gender match was better than those receiving a gender mismatch (P = 0.047). Female‐to‐male transplants had the worst graft survival of all combinations (P < 0.001); this difference was maintained in multivariate regression after adjustment for recipient and donor variables (hazards ratio 2.09, P = 0.013). Conclusion Female‐to‐male liver transplants are associated with a statistically significant poorer graft survival as compared with other donor‐recipient gender groups.